PEMERTAHANAN BAHASA IBU DI KAMPUNG MELAYU TANJUNG COLEM PULAU GALANG BATAM - Ambalegin Ambalegin; Tomi Arianto; Nurma Dhona Handayani (PUAN INDONESIA, 2021)
Indonesia is the second largest country with 652 local languages. Unfortunately, there are 11 local languages in Papua and Maluku that have become extinct based on the information of UNESCO. Thus, local language that is an identity and local wisdom must be preserved from the extinction. The locals in Pulau Galang Batam use Malay Galang as their everyday language. Having observed and conducted interviews to the elders in Kampung Melayu Tanjung Colem Pulau Galang Batam, it was identified that the speakers began to leave Malay Galang. The youngsters in Kampung Melayu Tanjung Colem Pulau Galang Batam used Indonesian with their peers and parents. Many of the local youngsters who left and returned Kampung Melayu Tanjung Colem Pulau Galang Batam did not use Malay Galang but Bahasa Indonesia. And the influence of language that appears on TV and Inter-ethnic marriages were the other factors of weak language-maintenance. Thus this activity aimed to educate the locals the importance of maintaining Malay Galang as an identity, heritage, and local wisdom and the importance of teaching Malay Galang to the youngsters so that Malay Galang does not become extinct. The method used was local community education program with the technique of lecturing and discussing. The result of this activity was the improvement of awareness and responsibility of the locals to maintain Malay Galang. Indonesia is the second largest country with 652 local languages. Unfortunately, there are 11 local languages in Papua and Maluku that have become extinct based on the information of UNESCO. Thus, local language that is an identity and local wisdom must be preserved from the extinction. The locals in Pulau Galang Batam use Malay Galang as their everyday language. Having observed and conducted interviews to the elders in Kampung Melayu Tanjung Colem Pulau Galang Batam, it was identified that the speakers began to leave Malay Galang. The youngsters in Kampung Melayu Tanjung Colem Pulau Galang Batam used Indonesian with their peers and parents. Many of the local youngsters who left and returned Kampung Melayu Tanjung Colem Pulau Galang Batam did not use Malay Galang but Bahasa Indonesia. And the influence of language that appears on TV and Inter-ethnic marriages were the other factors of weak language-maintenance. Thus this activity aimed to educate the locals the importance of maintaining Malay Galang as an identity, heritage, and local wisdom and the importance of teaching Malay Galang to the youngsters so that Malay Galang does not become extinct. The method used was local community education program with the technique of lecturing and discussing. The result of this activity was the improvement of awareness and responsibility of the locals to maintain Malay Galang.